Rancang Bangun Sistem informasi Akuntansi Penerimaan dan Pengeluaran Kas Pada BUMDes Agung Mandiri - Anggraeni, Neli Sri; Rahaningsih , Nining; Basysyar, Fadhil M (MEANS (Media Informasi Analisa dan Sistem), 2022)
Information systems are the most important part in a company or institution, one of which is an accounting information system for cash receipts and disbursements, which are usually used as support for decision making by management. BUMDes Agung Mandiri, which is engaged in services and trade, where the accounting information system for cash receipts and disbursements is still manual, therefore a computerized information system is needed to make work easier. The method used for reference in this research includes data collection techniques and system development techniques. Data collection techniques were observations, interviews, and literature research. Meanwhile, the system development technique uses a waterfall development model which consists of analysis, design, coding, testing, and maintenance. This research resulted in the design of cash receipts and disbursements accounting information systems that would facilitate the finance department in processing reports and also be used as a support for management in making decisions.